Predicting Urban trends of growth with Google Earth Engine - Islam, Rifah Tasmiah; Mim, Md. Shahriar; Tahiat Seeum, Nur Fathiha; Ahmed, Tahmina; Nawar, Tabassum Tanzim (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.